2011
DOI: 10.1021/np2004775
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoids and Coumarins from Glycyrrhiza uralensis: Antibacterial Activity against Oral Pathogens and Conversion of Isoflavans into Isoflavan-Quinones during Purification

Abstract: Phytochemical investigation of a supercritical fluid extract of Glycyrrhiza uralensis has led to the isolation of 20 known isoflavonoids and coumarins, and glycycarpan (7), a new pterocarpan. The presence of two isoflavan-quinones, licoriquinone A (8) and licoriquinone B (9), in a fraction subjected to gel filtration on Sephadex LH-20 is due to suspected metal-catalyzed oxidative degradation of licoricidin (1) and licorisoflavan A (2). The major compounds in the extract, as well as 8, were evaluated for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…T by about 30 and 70%, respectively, at 10 μg/ml [Gafner et al, 2011]. In that study, the growth media for S. mutans and S. sobrinus was ToddHewitt broth supplemented with hemin (10 μg/ml) and vitamin K (1 μg/ml), which may explain the discrepancy in antimicrobial efficacy of licorisoflavan A on S. mutans ATCC 25175…”
Section: -Methoxyficifolinol Licorisoflavan a And 68-diprenylgenimentioning
confidence: 91%
“…T by about 30 and 70%, respectively, at 10 μg/ml [Gafner et al, 2011]. In that study, the growth media for S. mutans and S. sobrinus was ToddHewitt broth supplemented with hemin (10 μg/ml) and vitamin K (1 μg/ml), which may explain the discrepancy in antimicrobial efficacy of licorisoflavan A on S. mutans ATCC 25175…”
Section: -Methoxyficifolinol Licorisoflavan a And 68-diprenylgenimentioning
confidence: 91%
“…Isoflavones of Glycyrrhiza uralensis were recently reported to have moderate growth-inhibitory properties against S. mutans . 16 Determination of the mechanism of action of flavonoids toward bacteria, which certainly differs from that of β-lactams, is an area of high interest. 27 The discovery of new compounds that exhibit good activity and diverse structure–activity relationships will likely contribute to these efforts.…”
mentioning
confidence: 99%
“…These findings could be useful in developing antibacterial agents from licorice and its various active phenolics. Besides the well-known traditional uses of licorice and the various reported biological effects [1][2][3][4][5][6][7][8], a recent study has added that several licorice phenolics exhibit higher tumor-specific cytotoxic effects [46]. However, further specific investigations on the safety of the pure licorice phenolics for human are awaited.…”
Section: Discussionmentioning
confidence: 99%
“…Potential beneficial effects of licorice in common oro-dental diseases were also discussed in a review article [4]. Potent antibacterial activities of licorice phenolics against bacterial strains such as Helicobacter pylori, cariogenic bacterial species, Streptococcus mutans and Streptococcus sobrinus, and periodontopathogenic species, Porphyromonas gingivalis and Prevotella intermedia, were also reported [5][6][7][8]. Our previous investigation revealed that several naturally occurring compounds showed potent antibacterial effects on methicillin-resistant Staphylococcus aureus (MRSA) [9][10][11], and some of the licorice phenolics, such as licoricidin (1), showed suppressing effects on the oxacillin resistance of MRSA [11].…”
Section: Introductionmentioning
confidence: 99%